Wear, roughness and microhardness analyses of single increment restorative materials submitted to different challenges in vitro - Oliveira, L. C. [UNESP]; dos Santos, P. H. [UNESP]; Ramos, F. S.S. [UNESP]; Moda, M. D. [UNESP]; Briso, A. L.F. [UNESP]; Fagundes, T. C. [UNESP] (Springer Nature, 2020)
Purpose: To evaluate the microhardness, roughness, profilometry and cross-sectional hardness of single increment materials submitted to different challenges. Methods: Thirty-six disks of each material, Filtek Supreme XTE (FT), Filtek One Bulk Fill (BK), Ketac Molar Easy Mix (KT) and Equia Forte + Coat (EQ) were immersed in saliva, pH cycling and Coke for 15 days. Half of each surface was used as its own control. Superficial microhardness, roughness, perfilometry analysis were performed. All samples were sectioned, embedded in acrylic resins, polished and cross-sectional hardness were made. Data were analyzed by ANOVA and Tukey’s test (p < 0.05). Results: The KT presented superficial microhardness superior than EQ. However, in depth, EQ showed superior values. FT, KT suffered the effects of challenges on microhardness values. The highest roughness and wear values were found for KT. RC do not suffer wear. All materials suffered the effects of Coke and pH challenges in depths 10 µm and 60 µm. Conclusion: The single increment restorative material that suffered less action on its surface was the bulk-fill resin. The coat present in the hybrid ionomer was able to resist to the immersion actions. In addition, Coke was the most aggressive challenge.
Keywords: Acids; Glass-ionomer cements; pH; Resin composite